Self-regulated in a Blended Learning: Case Study On Educational Doctoral candidates - Fitri April Yanti; Ahmad Walid; Habibi Habibi; M. Anas Thohir (IKIP Mataram, 2021)
This study investigates the use of self-regulated in blended learning by students in doctoral education courses to complete advanced statistics lectures. Self-regulated in blended learning is described in four phases according to Zimmerman, namely planning, monitoring, evaluation, and reinforcing. The participants consisted of five students from 5 different disciplines, and were willing to share their learning experiences. Research data obtained by interview method and analyzed qualitatively. Validation uses two strategies, namely member checking and peer debriefing. Member checking is done after the data is formulated into themes, then the researcher will bring it back to the participants to find out their accuracy. Peer debriefing was conducted by colleagues to review and ask critical questions about this research. Colleagues have at least a doctoral degree. The results show that planning for the completion of student assignments begins with (1) setting goals and planning strategies with (a) planning time for completing assignments; (b) Cooperation with peers online and off-line; and (c) planning for technical issues; (2) Regularly calculate their scores every week after being given feedback on the results of the lecturer's assessment, and save the feedback results from completed assignments; (3) using assignment assessment rubrics, using lecturer feedback, and grades, to measure progress in lectures; (4) the strategies they have designed and implemented have succeeded in making success in doing the task.